Pengaruh Jumlah Lilitan Groundstrap Pada Kabel Busi Terhadap Daya Dan Torsi Pada Sepeda Motor Supra 125 - Ubaidillah, Akhmad; Prasetyo, Imam; Setiawan, Sofian (Universitas Muhammadiyah Pekajangan Pekalongan, 2022)
installation of Groundstrap on spark plug wires as grounding spark plug wires so that the fire voltage from the coil will focus on the spark plugs. The increase in power and torque occurs because the groundstrap is a type of Ignition Booster whose function is to stabilize the electric current produced by the coil so that the spark plugs can be bigger and more stable, remove stray frequencies or indeterminate voltages from the coil, focus and narrow the current, so that it becomes a firing point towards the spark plug for use as a combustion flame. A steady current produces a good fire, so that the combustion explosion is complete. The method used in this study is the experimental method (direct trial) by making a Groundstrap circuit to determine power and torque in a motorcycle gasoline engine using a Dynotest tool for adding Groundstrap to spark plug wires. In this study using copper wire with a diameter of 0.6 mm and there were 3 variables for the number of turns of the groundstrap wire, namely 60 turns, 90 turns, and 120 turns. In 2008 there was an increase in general, the maximum power and torque yields for standard conditions were 8.3 HP and 8.79 NM, the test on winding 120 experienced the most significant increase of 1.7 HP from standard conditions to 10.0 HP and the torque reaches 3.95 NM from standard conditions to 12.74 NM Keywords: Groundstrap, Copper Wire Coil, Power and Torque